Analisa Faktor-Faktor yang Mempengaruhi Keputusan Nasabah Menggunakan Produk Perbankan (Studi Kasus Nasabah Bank Syariah Indonesia Kantor Cabang Pembantu Muara Bulian) - Sumantri Sumantri; Diyah Diyah; Albetris Albetris (Universitas Batanghari Jambi, 2021)
This research aims to determine the influence of services, bank characteristics, knowledge, location on customer decisions using Bank Syariah Indonesia (Case Study of Muara Bulian Central Branch Office). This study used sampling techniques with a sample of 100 customers of Bank Syariah Indonesia Muara Bulian Sub-Branch Office. This research method is to use qualitative research method with the help of SPSS application as a data calculation tool that has been able to. This study uses 4 variables, namely service, bank characteristics, knowledge, location. The results of this study show that partially the Characteristics of the Bank are very influential to customer decisions by 4.87, and become the most dominant factor, the Service affects customer decisions by 4.11, Knowledge is quite influential on customer decisions by 3.4, and Location affects customer decisions by 3.9.